A Dual Elasticity of Substitution Production Function with an Application to Cross Country Inequality - Juergen Antony (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
This paper develops a production function which two separate elasticities of substitution between two input factors. One of these elasticities is obtained if the factor intensity equals a particular baseline value. The second part of the paper gives an economic application and shows the theoretical properties of this production function regarding the development of relative capital intensities and relative production per efficiency unit of labor. Inequality across countries widens in transition to the steady state. Panel data on the development of these relative figures seem to support the implications of the above production function.
Keywords: O11; O33; E23; 330; Capital and labor substitution; cross country inequality